2023
DOI: 10.1097/md.0000000000033674
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spinal alignment one month post abdominal surgery: A prospective cohort study

Abstract: Following abdominal surgery, many patients assume a bending or stooping posture to protect the surgical wound. Such postural changes are known to induce side effects, but the improvement and persistence of these effects are unknown. Therefore, the purpose of this study was to clarify the nature of postural changes in patients undergoing abdominal surgery. In this prospective cohort study, we enrolled 25 patients who underwent abdominal surgery from February 2019 to January 2020. Measurements were obtained duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Although studies on postoperative changes in the spine due to other surgical methods have been reported in vivo ( 11 ), the only studies that have examined the effects of a mid-thoracic incision on the spine have used thoracic spine specimens ( 12 - 14 ). Therefore, the range of motion in vivo , including soft tissues and surrounding muscles, has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on postoperative changes in the spine due to other surgical methods have been reported in vivo ( 11 ), the only studies that have examined the effects of a mid-thoracic incision on the spine have used thoracic spine specimens ( 12 - 14 ). Therefore, the range of motion in vivo , including soft tissues and surrounding muscles, has not been examined.…”
Section: Introductionmentioning
confidence: 99%